ANALISIS PILIHAN SALURAN PEMASARAN INDUSTRI AMPLANG: STUDI KASUS DI KECAMATAN SANGA-SANGA KABUPATEN KUTAI KARTANEGARA - Megawati Ayuningsih; Bambang Indratno Gunawan; Muhammad Syafril (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
This research aims to: (1) analyze the effect of factors selling price, profit and business duration to marketing channel choice and (2) identify main problems facing in the local fish cracker or ‘amplang’ product in Sanga-Sanga District. Research method applied in this research was survey method and field observation with census approach as sampling technique and interviews. Data were analyzed by both qualitative and quantitative approach with the number of respondents were 11 people those distributed within five districts. Results showed that based on the likelihood ratio test or simultaneous test it was known selling price and profit variables significantly affect to producers’ choice of to choose amplang industry marketing channel (α=5%) meanwhile years of bussiness does not affect it. In addition, according to logistic multinomial regression it was seen that selling price, profit and years of business do not affect partially to marketing channel of amplang product both in the logit equation 1 and the equation 2. Main problems identified in amplang product marketing performance were raw material supply, labor force limitation, the implementation of P-IRT and halal label, and the product promotion discontinuity. Key words: amplang, logistic multinomial regression, marketing channel, Sanga-Sanga